Economic Empowerment of Farmers through Adoption of Vegetable Cultivation Technology in Hadoti Region of Rajasthan - Navab Singh, A. K. Verma , K. L. Jeengar, Pankaj Seth , R. R. Meena and B. L. Meena, (Indian Journal of Extension Education, 2017)
The study was undertaken in Jhalawar district of Rajasthan. Data were solicited from randomly selected 60 beneficiaryand 60 non-beneficiary vegetable growers of Krishi Vigyan Kenddra (KVK) Jhalawar district, Rajasthan, India. Theimportant interventions extended by KVK Jhalawar among farmers were vegetable varieties, time of sowing, plantprotection measures, and fertilizer application. Findings of the study revealed that technological interventionsextended by KVK have significantly empowered the vegetable growers technologically and economically. Higherextent of adoption of timely sowing, balanced fertilizer use and plant protection measures by the beneficiaryrespondents resulted in less cost of cultivation (Rs. 8,350/-) and higher net income (Rs.1,04,200/-) from vegetablecultivation than the non-beneficiary respondents.